Ibn Khaldun’s Linguistic Contributions in Light of Modern Linguistic Studies - ounougi, ismail (El Omda in Linguistics and Discourse Analysis, 2018)
The Arab heritage is rich with sciences and arts that many researchers have overlooked. Perhaps for this reason, some emerging scholars have even denied the contributions of classical Arab scholars, despite their significant role in establishing a vast array of Arabic grammar rules, compiling immense collections of poetry across various genres, and creating numerous artistic forms whose influence remains strong to this day. For this reason, I aim to shed light on a small example of these many Arab scholars whose impact on different fields of Arab studies—literary or linguistic—was clear and whose influence extended to both Arabs and non-Arabs. Among them is ‘Abd al-Rahman Ibn Khaldun, particularly in his famous Muqaddimah, which continues to be studied and drawn upon today. Notably, many of the theories it presents closely align with principles advocated by modern theories in education, politics, sociology, and other fields.